Reducing fear of water and aquaphobia through 360 degree video use? - Roche, Lionel; Cunningham, Ian; Rolland, Cathy; Fayaubost, Régis; Maire, Sébastien (Frontiers in Education, 2022)
Drowning is a serious public health problem threat claiming the lives of 372,000 people each year worldwide that can be linked to an individual’s ability to swim. Learning to swim requires limited fear of water. This exploratory study investigated the potential interests of 360° video use for reducing fear and apprehension that underpin aquaphobia. Two students aged 11–12 years old who were non-swimmers with a reluctance to enter the water (i.e., a refusal and/or fear of immersion or to immerse only part of the face or the body in water) participated in qualitative interviews while viewing 360° video of an aquatic environment at progressively deeper levels through a head-mounted display (HMD). Three main findings were identified. First, the use of a 360° video viewed in an HMD led students to live an original corporeal immersive experience, a kind of immersion in the pool but experienced outside the pool. Second, students felt a strong emotional engagement between anxiety and curiosity from exploring the aquatic environment. Third, during the viewing situation, students developed and acquired accurate perceptive cues and knowledge related to the aquatic environment. The implications of these findings highlight the benefits of 360° video use as a tool to enhance greater confidence and familiarity with the aquatic environment to support learning and reduce phobia in non-swimmers. Limitations of the study and future research directions are discussed.